Japan : IOSCO Objectives and Principles of Securities Regulation: Detailed Assessment of Implementation. (IMF Staff Country Reports; Country Report ;, 2012)
This report analyzes the functioning of the legal and regulatory framework for the securities market in Japan. The Financial Services Agency (FSA) enjoyed specific powers with respect to the various security laws and regulations laid down by the International Organization of Securities Commission (IOSCO). The FSA has been authorized to bring about certain changes, to implement new principles, and to develop new frameworks to ensure and strengthen the smooth functioning of supervision and investigation. It is also necessary to identify and assess risks to determine FSA intervention.